O impacto dos movimentos históricos na pesquisa em estudos organizacionais no Brasil - Gomes, Silmara Cristiane (2011)
The organizational studies researches have changed focus over the years, the changes observed are largely influenced by the environment and the way individuals understand the world. One of the influencers, from both the environment and the way individuals see the world, are the historical events. Events like Second World War changed the way individuals see and understand the world and other individuals, restructured geographical areas and political and social environments. These changes have generated and generate changes in organizational studies perspectives, all around the world. To understand if organizational studies, in Brazil, were affected by historical events, similar to those that influenced research changes in this area in other parts of world, was the initial motivation of this work. The objective was to verify whether the organizational studies researches, in Brazil, suffered the impact of historical world events, in the past decades. To achieve this goal, several articles in two journals were analyzed, the journal RAE - Revista de Administração de Empresas, of Getúlio Vargas Foundation, and the journal RAUSP, Revista de Administração, of the São Paulo University, available on the Internet, in the years from 1965 until 2009. Through a parallel between the approaches indicated by March (2007), to determine characteristics that reflect the historical events impact in the organizational studies researches, and identified characteristics in Brazilian studies, this study aimed to show how Brazilian researches reflects some Historical events impacts